Mesenchymal stem cell enhances chondral defects healing in horses - Yamada, Ana Lucia Miluzzi [UNESP]; Carvalho, Armando De Mattos; Moroz, Andrei [UNESP]; Deffune, Elenice [UNESP]; Watanabe, Marcos Jun [UNESP]; Hussni, Carlos Alberto| [UNESP]|Rodrigues, Celso Antônio [UNESP]; Alves, Ana Liz Garcia [UNESP] (Scientific Research Publishing, 2013)
The purpose of this study was to evaluate the effect of intralesional Mesenchymal Stem Cells (MSC) on the treatment of experimentally induced articular chondral defects in horses, emphasizing the benefits of this application in veterinary medicine. Chondral defects were induced in the medial femoral trochlea of both hind limbs of four horses. Thirty days post induction; the horses were divided into two groups. The G1 was submitted to treatment with MSC and the G2 was the control group. Clinical evaluations, synovial fluid analysis and synovial Prostaglandin E2 (PGE2) assessment were performed prior to defects and fortnightly up to 120 and 150 days. Macroscopic, histopathological and histochemical evaluations were performed at the end of the experiment. The treatment with MSC reduced the intraarticular inflammatory process. The G1 showed lower PGE2 concentrations in the synovial fluid and greater percentage of mononuclear cells and lower percentages of lymphocytes and neutrophils. The treatment improved the macro and microscopic aspects of repair tissue. No difference was observed in the scores of lameness between the G1 and G2. The use of MSC in the treatment of chondral defects minimized joint inflammation, as confirmed by synovial fluid analysis. The treatment resulted in an improved repair tissue, verified by macroscopic examination, histochemical and histopathological analysis.
Keywords: Arthroscopy; Cartilage; Equine; Lameness; Mesenchymal stem cells